The Monitor project: rotation periods of low-mass stars in M50 - Irwin, Jonathan; Aigrain, Suzanne; Bouvier, Jerome; Hebb, Leslie; Hodgkin, Simon; Irwin, Mike; Moraux, Estelle (Monthly notices of the Royal Astronomical Society, 2009)
We report on the results of a time-series photometric survey of M50 (NGC 2323), a ∼130 Myr open cluster, carried out using the Cerro Tololo Inter-American Observatory (CTIO) 4-m Blanco telescope and Mosaic-II detector as part of the Monitor project. Rotation periods were derived for 812 candidate cluster members over the mass range 0.2 ≲M/M⊙≲ 1.1. The rotation period distributions show a clear mass-dependent morphology, statistically indistinguishable from those in NGC 2516 and M35 taken from the literature. Due to the availability of data from three observing runs separated by ∼10 and 1 month time-scales, we are able to demonstrate clear evidence for evolution of the photometric amplitudes, and hence spot patterns, over the 10 month gap. We are not able to constrain the time-scales for these effects in detail due to limitations imposed by the large gaps in our sampling, which also prevent the use of the phase information.